2015
DOI: 10.1136/heartjnl-2014-307253
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of silent atrial fibrillation after acute myocardial infarction at 1-year follow-up

Abstract: Our large prospective study showed for the first time that silent AF is associated with worse 1-year prognosis after AMI. Systematic screening and specific management should be investigated in order to improve outcomes of patients after AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…Patients with AF develop during the hospital period are older as well as with higher rate of hypertension (HTA) and heart failure (HF) which may contribute to the worse outcome [1,2,79,1216] Atrial fibrillation may precipitate the occurrence of severe ventricular arrhythmias which may lead to sudden death in these patients [17]. The large numbers of research has been done in patients with ST-elevation myocardial infarction (STEMI), but some studies have also included patients [1821] with non-ST-elevation myocardial infarction (NSTEMI) [12,17,22]. However, there are a small number of research that examined the association between AF develops during the hospital period and clinical outcomes among patients with both STEMI and NSTEMI [2].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with AF develop during the hospital period are older as well as with higher rate of hypertension (HTA) and heart failure (HF) which may contribute to the worse outcome [1,2,79,1216] Atrial fibrillation may precipitate the occurrence of severe ventricular arrhythmias which may lead to sudden death in these patients [17]. The large numbers of research has been done in patients with ST-elevation myocardial infarction (STEMI), but some studies have also included patients [1821] with non-ST-elevation myocardial infarction (NSTEMI) [12,17,22]. However, there are a small number of research that examined the association between AF develops during the hospital period and clinical outcomes among patients with both STEMI and NSTEMI [2].…”
Section: Introductionmentioning
confidence: 99%
“…Для оценки выраженности симптомов, сопровождающих ФП, была разработана шкала EHRA [21]. Согласно ре-комендациям Европейского общества кардиологов, асимптомная, или «немая» ФП часто встречается в общей популяции [22,23], а по данным ряда иссле-дований -у пациентов с ИМ в 3 раза чаще симптом-ной ФП [24,25].…”
Section: New-onset Atrial Fibrillation In Acs впервые возникшая фибриunclassified
“…Пароксизмы ФП, сопровождающиеся симптомами, среди общей группы составили 4,3%. ФП в анамнезе обнаруживалась среди 10% в группе «немой ФП», а в группе с «симптомной ФП» -среди 38% больных (p<0,001) [24].…”
Section: New-onset Atrial Fibrillation In Acs впервые возникшая фибриunclassified
“…47 It was previously suggested that silent AF was three times more common than symptomatic AF after acute MI. 48 This highlights importance of continuous ECG monitoring for all patients with MI to detect AF.…”
Section: Prognosis Of Silent Af After Myocardial Infarctionmentioning
confidence: 99%